Comparison of SpO2/FiO2 ratio and PAO2/FIO2 ratio as initial assessment in patients at risk of respiratory failure - Nohu, Mohammad Gilang Fajriansyah; Satriawan Abadi; Harun Iskandar; Syakib Bakri; Hasyim Kasim; Andi Alfian Zainuddin (Acta Biomedica Atenei Parmensis, 2025)
Introduction: The risk of respiratory failure such as shortness of breath which causes difficulty in the breathing process, if not treated properly can result in respiratory failure, then organ failure with high morbidity and mortality. These risks can be identified by measuring oxygen saturation with oximetry. The purpose of this study is to determine and examine the comparison of the Oxygen saturation/Fraction of inspired oxygen (SpO2/FiO2) ratio and the Partial pressure of oxygen /Fraction of inspired oxygen (PaO2/FiO2) ratio as an initial assessment in patients at risk of respiratory failure. Methods: Cross-sectional study conducted among patients in the emergency room and treatment room at Wahidin Sudirohusodo Hospital Makassar and its network with symptoms of shortness of breath. The data collected from the results of blood gas analysis, oxygen saturation examinations, and patient medical records. Results: A total of 103 samples were obtained with an age range of 20-87 years. Based on the data, the mean SpO2 value was 95.7%, PaO2 was 163.3 mmHg, FiO2 was 70.7%, SpO2/FiO2 ratio was 175.1 mmHg and PaO2/FiO2 ratio was 332.2 mmHg. The threshold value of the SpO2/FiO2 ratio for respiratory failure of 281 corresponds to the PaO2/FiO2 ratio of 300 with a sensitivity of around 93% and a specificity of 96%. Conclusion: The SpO2/FiO2 ratio was strongly correlated with the PaO2/FiO2 ratio in assessing respiratory failure. So, the SpO2/FiO2 ratio can be used as an alternative to the PaO2/FiO2 ratio for early detection in patients at risk of respiratory failure.